Frequência e gasto escolar das famílias brasileiras no ensino básico: Evidência microeconômica com a POF 2017-2018 - Marcos Antonio Coutinho da Silveira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– Using data from the 2017-2018 Households Budget Survey, the work investigates the demographic and socioeconomic determinants of the Brazilian families investment in the basic education of their school-age members, which is processed through three sequential decisions: school attendance, the option between public and private school (i.e., whether or not it incurs positive school spending) and the size of school spending. As a result of this sequential structure, a double sample selection bias model is estimated separately for the three education levels (preschool, elementary-middle school and high school) in order to correct any sample selection biases arising from the correlation between unobserved factors in those three decisions. Consistent with the evidence found in other countries, that investment is positively affected by the level of education of those responsible for the family, the per-capita family income and the quality of education available. An effect in the opposite direction is observed in relation to the distance between the family's residence and the capital of their State. Other variables with a significant effect are the color and the predominant job occupation in the family, the gender of school-age members, the geographic region and size of the family, as well its age composition.
Keywords: D1; E2; I2; 330; basic education; school attendance; school spending